Roles of Ceramides in Non-Alcoholic Fatty Liver Disease - Hajduch, Eric; Lachkar, Floriane; Ferré, Pascal; Foufelle, Fabienne (Journal of clinical medicine, 2021)
Non-alcoholic fatty liver disease is one of the most common chronic liver diseases, ranging from simple steatosis to steatohepatitis, fibrosis, and cirrhosis. Its prevalence is rapidly increasing and presently affects around 25% of the general population of Western countries, due to the obesity epidemic. Liver fat accumulation induces the synthesis of specific lipid species and particularly ceramides, a sphingolipid. In turn, ceramides have deleterious effects on hepatic metabolism, a phenomenon called lipotoxicity. We review here the evidence showing the role of ceramides in non-alcoholic fatty liver disease and the mechanisms underlying their effects.